Dr. John D. Perry, 1918. - Farrell's Studio (Forsyth County Public Library, 1918)
Source: Booklet, "Winston-Salem, City of Industry," 1918.
Dr. John D. Perry, 1918. Dr. Perry was a optometrist.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth